Identifikasi Visual Morfologis sebagai Strategi Kuratorial dalam Pengelolaan Koleksi Keris Museum Majapahit Trowulan - Bening Tri Suwasono; Sunarmi Sunarmi; Devi Nirmala Muthia Sayekti (Lembaga Pengembangan Kinerja Dosen, 2025)
The Majapahit Museum houses a significant collection of tosan aji, particularly keris, which holds important historical, technological, and symbolic value within Javanese culture. However, a substantial portion of the collection lacks clear provenance and stratigraphic context, resulting in data gaps and potential misinterpretations, especially regarding Majapahit-period attribution. This study aims to examine strategies for managing non-stratigraphic keris collections through standardized visual-morphological identification as an initial curatorial approach. The research employs direct artifact observation, morphological analysis of blades and ricikan, visual examination of pamor configurations, and a review of museological, keris studies, and archaeometallurgical literature. The findings demonstrate that standardized morphological identification provides a systematic framework for preliminary classification while preventing speculative chronological claims. The study also emphasizes the necessity of separating blade analysis from keris fittings and highlights the limitations of visual assessment in determining tangguh, which requires support from non-destructive metallurgical analyses. As a practical contribution, this article proposes strengthening curatorial standards through the development of morphology-based artifact labels (manual and digital), multidisciplinary scholarly catalogues, and the integration of documentation and material analysis technologies. This approach positions the Majapahit Museum as a knowledge-producing institution in tosan aji studies rather than merely a repository of artifacts. Kata Kunci : Museum Majapahit, Keris, Identifikasi Morfologis, Ricikan, Tangguh Keris